2014
DOI: 10.1007/s12648-014-0569-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of N-doped ZnO and N–Al codoped ZnO thin films deposited by pulsed filtered cathodic vacuum arc deposition

Abstract: N-doped ZnO and N-Al codoped ZnO films are deposited onto glass substrate at room temperature by pulsed filtered cathodic vacuum arc deposition system. The films are characterized by X-ray diffraction, Raman spectra, UV-Vis-NIR spectrophotometer, atomic force microscopy (AFM) and Hall measurements. Films are textured along the (002) direction. AFM images reveal that surface of N-Al codoped ZnO film grown at RT is smoother than that of the N-doped ZnO (ZnO:N) film. Optical band gap of the N-Al codoped ZnO film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Additionally, the (002) crystal face exhibited the strongest peak among all samples, suggesting all the ZnO-based samples grew along the C-axis. Compared with the undoped ZnO samples, the dominant peak (002) of N-doped and Al-N-co-doped ZnO samples slightly shifted towards a lower diffraction angle, while the dominant peak of Aldoped ZnO sample shifted slightly towards a higher diffraction angle (Figure 3c), indicating that Al and N atoms were incorporated into the ZnO lattice [24][25][26]. (HR)TEM and EDS mapping images of the undoped, Al-doped, N-doped, and Al-Nco-doped ZnO nanorods are shown in Figure 4.…”
Section: Morphologic and Structural Characterizations Of The Undoped ...mentioning
confidence: 98%
“…Additionally, the (002) crystal face exhibited the strongest peak among all samples, suggesting all the ZnO-based samples grew along the C-axis. Compared with the undoped ZnO samples, the dominant peak (002) of N-doped and Al-N-co-doped ZnO samples slightly shifted towards a lower diffraction angle, while the dominant peak of Aldoped ZnO sample shifted slightly towards a higher diffraction angle (Figure 3c), indicating that Al and N atoms were incorporated into the ZnO lattice [24][25][26]. (HR)TEM and EDS mapping images of the undoped, Al-doped, N-doped, and Al-Nco-doped ZnO nanorods are shown in Figure 4.…”
Section: Morphologic and Structural Characterizations Of The Undoped ...mentioning
confidence: 98%
“…In the previous papers on ZnO thin films grown by PFCVAD, it has been demonstrated that such films have low resistivities and high optical transmittances in the UV/visible region [28][29][30][31]. To date, the optical and structural properties of unintentionally n-doped ZnO thin films, the effect of growth conditions on the quality of ZnO thin films, and p-type doping of ZnO thin films grown by PFCVAD have been studied by Senadim and Kara et al [32][33][34]. Kara et al also reported that post-thermal annealing of ZnO thin films grown by PFCVAD improves the crystal quality, changing the structure of ZnO:Al from amorphous to crystalline upon annealing at 600 °C [33].…”
Section: Introductionmentioning
confidence: 99%